HEGEMONI POSITIVISME TERHADAP PENDIDIKAN DI INDONESIA - Andit Triono, Muhammad Rafi’i, Desinta Setiani (Journal Analytica Islamica, 2020)
Abstract: Epistemology in philosophy is an integral part of the construction of knowledge in this world. This epistemology develops later as a design in producing a science. The presence of positivism, which was popularized by Auguste Comte, then complements the two stumps of the basic epistemological philosophies that have developed long before, namely rationalism and empiricism. As a bridge between rationalism and empiricism, positivistic epistemology then appeared to bring colors that were so thick with modern knowledge, even though the tendency was towards empiricism. This positivistic epistemology later became the king of knowledge in the world's formal educational institutions, except in Indonesia. The existing curriculum footprints are indeed thick with the positivistic direction this epistemology contains. The presence of the latest curriculum cannot escape the grip of positivism, and it has always been an important part of evaluation and research.Keywords: Positivism, Educational Curriculum, Educational Trends